Alum adjuvanted rabies DNA vaccine confers 80% protection against lethal 50 LD50 rabies challenge virus standard strain. (May 2017) - Garg, Rajni; Kaur, Manpreet; Saxena, Ankur; Prasad, Rajendra; Bhatnagar, Rakesh
Highlights: We had previously developed lysosome targeted, glycoprotein based rabies DNA vaccine (RDV), which conferred protective immunity in BALB/c mice upon lethal challenge. We had also established its pre-clinical safety as per various guidelines. For clinical application, we investigated the vaccine formulation with FDA approved adjuvants; Alum, Immuvac and Montanide ISA720 VG. Enhanced immune response correlated with Th2 biased, high IgG antibody titer as well as RVNAs upon Alum supplementation of the RDV. Furthermore, the alum adjuncted DNA vaccine conferred 80% protection against challenge with 50 LD50 of the rabies CVS strain. Thus, this rabies DNA vaccine, pgp.LAMP-1, has established its safety profile as well as potency; and in conjunction with alum may be effective for mass immunization. Abstract: Rabies is a serious concern world-wide. Despite availability of rabies vaccines for long; their efficacy, safety, availability and cost effectiveness has been a tremendous issue. This calls for improvement of rabies vaccination strategies. DNA vaccination has immense potential in this regard. The DNA vaccine pgp.LAMP-1 conferred 60% protection to BALB/c mice against 20 LD50 rabies challenge virus standard (CVS) strain challenge. Upon supplementation with Emulsigen-D, the vaccine formulation conferred complete protection against lethal challenge. To assess the feasibility of this vaccine formulation for human use, it was tested along with other FDA approved adjuvants, namely, Alum, Immuvac, Montanide ISA720 VG. Enhanced immune response correlated with high IgG antibody titer, Th2 biased response with a high level of rabies virus neutralizing antibodies (RVNAs) and IgG1/IgG2a ratio >1, observed upon alum supplementation of the rabies DNA vaccine. The total IgG antibody titer was 2 IU/ml and total RVNA titer was observed to be 4 IU/ml which is eight times higher than the minimum protective titer recommended by WHO. Furthermore, it conferred 80% protection against challenge with 50 LD50 of the rabies CVS strain, conducted in compliance with the potency test for rabies recommended by the National Institutes of Health (NIH), USA. Previously, we have established pre-clinical safety of this vaccine as per the guidelines of Schedule Y, FDA as well as The European Agency for evaluation of Medicinal Products. The vaccine showed no observable toxicity at the site of injection as well as at systemic level in Wistar rats when administered with 10X recommended dose. Therefore, supplementation of rabies DNA vaccine, pgp.LAMP-1 with alum would lead to development of a non-toxic, efficacious, stable and affordable vaccine that can be used to combat high numbers of fatal rabies infections tormenting developing countries.